Evaluation of Digital Economy Growth: the Validity of the Data Envelopment Analysis (DEA) Method - Adinata, Patrick Vivid (East Asian Journal of Multidisciplinary Research, 2024)
This research aims to provide methodological insights that can be used in related studies, as well as offer guidance for the development and improvement of urban digital economies. Gross Domestic Product (GDP)-based scale measurement methods and input-output methods show significant variations in the measurement of digitalisation and the contribution of the digital economy. While index techniques offer convenience in the calculation and expansion of indicators, their accuracy and scientific validity are often in doubt due to subjectivity in the weighting and selection of indicators. DEA offers great flexibility by allocating input and output weights endogenously, reducing the influence of subjectivity. DEA is able to identify fast-growing cities in the digital economy, assess effectiveness, and provide strong support for managerial decision-making, as well as provide guidance for the development of smarter and more efficient cities in the future. This research makes a practical contribution to the development of more appropriate and effective digital economy policies and strategies.